Comparison of BRCA1 Gene Expression and CA15-3 Tumor Marker Level in Different Stages of Breast Cancer - Negar Soltani Irdmusa; Haniyeh Bashi Zadeh Fakhar; Masoumeh Heshmati; Mohammad Esmaiel Akbari; Sara Rahimi (The Breast Journal)
Breast cancer (BC), a globally prevalent malignancy, shows significant variability in incidence across different geographical regions. In this study, we examined the expression of the tumor suppressor gene BRCA1 and the tumor marker CA15-3 in women diagnosed with BC, focusing on different cancer grades. Our research, conducted at the Baqiyat Elah Hospital in Tehran in 2021, involved collecting blood and serum samples from BC patients. These samples underwent BRCA1 gene expression analysis and CA15-3 tumor marker assessment. Using the AJCC grading system, we categorized BC patients into various grades. Our findings revealed that BRCA1 gene expression was present in 28.57% of patients, while 71.43% showed negative expression. Both BRCA1 expression and CA15-3 levels significantly increased with advanced cancer stages (P<0.001). These results suggest the potential utility of BRCA1 gene expression and CA15-3 tumor marker assessment in BC prognosis and management, particularly concerning staging and disease progression. This study provides valuable insights into the biology of BC and the development of prognostic markers for improved patient outcomes.